Perceived Impact of Social Media on Panic Buying: An Online Cross-Sectional Survey in Iraqi Kurdistan - Arafat, S.M. Yasir; Ahmad, Araz Ramazan; Murad, Hersh Rasool; Kakashekh, Hardawan Mahmoud (Frontiers in Public Health, 2021)
Background: Social media has an impact on panic buying by creating fear, disseminating pictures, and videos of people purchasing extra goods in a state of panic during the COVID-19 pandemic. Aim: We aimed to evaluate the perceived impact of social media on panic buying behaviors in the Iraqi Kurdistan region. Methods: This cross-sectional survey was conducted from October 10 to November 25, 2020. A self-reported instrument was designed in English and then translated to the Kurdish Language to conduct the study. It was disseminated through social media platforms (Facebook, Viber, and WhatsApp) and e-mail, via a link and 466 responses were collected from social media users. The statistical computations were performed using SPSS version 21. Results: The majority of respondents were male (62.2%), less than 25 years old (43.9%), had completed their bachelor’s degree (53.9%), and most of the respondents (86.3%) used Facebook. Among the respondents, 42.1% were involved in panic buying, 32.8% of the respondents thought that social media platforms had an influence on panic buying, 86.1% of the respondents thought that social media should be sensible while reporting it, 88.4% thought that the reporting should be controlled, and 78.5% thought that photos of empty shelves should be avoided. There was a significant positive statistical correlation (r = 0.84) between social media use and panic buying among consumers during the COVID-19 pandemic in Iraqi Kurdistan (p = <0.001). Conclusion: This research assessed how social media affects buying behavior, particularly in Iraq. Collective measures, such as sensible use and adequate media literacy, are needed to prevent such behaviors at least during public health emergencies.